Notifiche
Cancella tutti

Frazione

  

0

6/5-(7/11-1/5)x(5/7+1/14)

Autore
2 Risposte



1

6/5 -  (7/11 - 1/5 ) x (5/7 + 1/14) =

mcm (11; 5) = 55;  mcm (7;14) = 14;

 

= 6/5 -  (35/55 - 11/55) x (10/14 + 1/14) =

= 6/5 - 24/55 x 11/14 =

= 6/5 - (24 x 11) /(55 x 14) ;     (11 si semplifica con 55, resta 1/5;  24 si semplifica con 14 , si semplifica per 2;  resta 12/7);

= 6/5 - (12 x 1) /(5 x 7) =

= 6/5 - 12/35=

mcm(5; 35) = 35;

= 42/35 - 12/35 =

= 30/35 = (semplificando per 5):

= 6/7.

Ciao  @gianvi

 



0
IMG20241125064356



Risposta
SOS Matematica

4.6
SCARICA